Positron spectroscopy of defects in hydrogen-saturated zirconium - Bordulev Yu. S. Yuri Sergeevich; Laptev R. S. Roman Sergeevich; Kudiyarov V. N. Victor Nikolaevich; Lider A. M. Andrey Markovich (2015, 2015)
Title screen